CO2 reforming of methane to syngas over CoOx/MgO supported on low surface area macroporous catalyst carrier: Influence of Co loading and process conditions - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Industrial & Engineering Chemistry Research, 2006)
The effect of Co loading (5-30 wt %) and process parameters ( reduction pretreatment, reaction temperature, and space velocity) have been investigated over CoOx/MgO(5%)/SA-5205 catalyst for the CO2 methane reforming process. The Co loading had a profound effect on the methane conversion and the hydrogen selectivity ( initial and time-on-stream activity) for the unreduced catalysts. While negligible methane conversion was observed for the 5 and 10 wt % Co loading catalyst, methane conversions > 95% were obtained over the high Co loading ( 20 and 30 wt %) catalysts; hydrogen selectivity followed the same trend as methane conversion. The Co loading level had a relatively smaller influence in the case of the reduced catalysts. While the 5 wt % Co catalyst showed low methane conversion activity (< 30%), the 10 wt % Co catalyst showed methane conversion levels comparable to those of the high Co loading catalysts. The high Co loading catalysts showed an excellent time-on-stream performance for the CO2 methane reforming reaction. X-ray diffraction and temperature-programmed reduction experiments indicate that the interesting activity behavior exhibited by the catalysts is related to the different phases ( and their reducibility) present in the catalysts at different Co loadings. The hydrogen selectivity was found to decrease with decreasing reaction temperature and increasing space velocity due to the increased simultaneous occurrence of the reverse water-gas shift reaction along with the CO2 reforming reaction.